La práctica deportiva y la formación integral de los estudiantes de la institución educativa primaria y Secundaria N° 6010148 Balbina Dora Soto Correa, Distrito Ramón Castilla 2024 - Leonardo Tangoa, Erika Margot (2025)
The general objective of this research was to determine the relationship between sports practice and the integral formation of primary school students of the I.E.P.S.M. N° 6010148 Balbina Dora Soto Correa, district Ramón Castilla 2024. Opting for a study of basic type, with a correlational level and a transversal non experimental design; the sample was confirmed by 100 students for the accomplishment of the survey conducted by two questionnaires for the collection of data. The findings show that 73% have adequate sporting practice; 76% have an adequate education in terms of comprehensive training. Therefore, it is determined that between the variables there is a significance p=0.000 (<0.05).